APRIMORAMENTO DE TECNOLOGIAS PARA ELABORAÇÃO DE PRODUTOS DERIVADOS DE SOJA E LEITE COM PROBIÓTICOS - FIORENTINI, ANGELA M.; BALLUS, CRISTIANO A.; OLIVEIRA, MARLON L. D.; CUNHA, MÁRCIO F.; KLAJN, VERA M. (Salão do Conhecimento, 2013)
Resumo